Psychometric assessment of the Beck anxiety inventory and key anxiety determinants among Ukrainian female refugees in the Czech Republic - Iryna Mazhak; Iryna Mazhak; Danylo Sudyn (Frontiers in Psychology)
IntroductionThe full-scale Russian war has caused Ukrainian female refugees to experience many stressful events which may have an adverse impact on their mental health. Understanding the prevalence and determinants associated with anxiety is essential for psychosocial support. The study aimed: to evaluate the psychometric validity of the Ukrainian version of the Beck Anxiety Inventory (BAI) among Ukrainian female refugees in the Czech Republic, to determine the prevalence of anxiety, and to identify key determinants for anxiety in this population.MethodsAnxiety was measured by BAI, which was validated by applying confirmatory factor analysis. Linear regressions were run to understand associations between social, physical and mental health determinants and anxiety, adjusted by socio-demographics.ResultsThe BAI had a high level of internal consistency. External consistency was confirmed through: structural validity via CFA, indicating that a four-factor model, including cognitive, autonomic, neuromotor, and panic factors, were the most appropriate for the Ukrainian version of BAI; and convergent validity, shown by significant correlations between the total scores of the BAI and coping strategies, perceived stress, depression as well as self-reported physical and mental health. The study revealed that more than half of the participants had moderate to concerning symptoms of anxiety. The analysis indicated that poor perceived health, ineffective coping strategies, high perceived stress, and hampered daily activities due to health issues, are significant predictors of increased anxiety. Conversely, positive or stable social relations with relatives, neighbors, and locals, and the absence of discrimination, were shown to be crucial in reducing anxiety levels.